CELAH INTERVENSI KEKUASAAN EKSEKUTIF TERHADAP KEKUASAAN YUDIKATIF DI LINGKUNGAN PERADILAN MILITER - Sanjaya, Aditya Wiguna (Jurnal Panorama Hukum, 2018)
Judicial power is one of the pillars supporting the establishment of a state, which ideally upholds the principle of independence so that it is independent and free from any influence of power, in the context of Indonesia the judicial power is carried out by a Supreme Court consisting of four judicial circles, namely general justice, religious court, the administrative court, military court and a Constitutional Court, in the course of the dynamics in the implementation of Judicial Power in Indonesia, which initially involved the organization, administration, and finance of the judicial body in relation to subordinate executive power, after the reform era had shifted under the Supreme Court, however, specifically for the military court there are still gaps in the potential for intervention from the executive power, which are caused by judges in the military court hierarchically there is still a command relationship with the TNI Commander and the President as the highest authority over the TNI. This will certainly have an influence on the independence of the military court as one of the executive branches of judicial power.